Cognitive multi-cell visible light communication with hybrid underlay/overlay resource allocation - Yang, Helin (2020)
In order to improve the spectral efficiency of indoor visible light communication (VLC) systems, in this letter, motivated by the concept of cognitive radio, we propose a new multi-cell cognitive VLC (C-VLC) system. The proposed multi-cell C-VLC system is comprised of both primary users and secondary users (SUs), by defining them based on users' service requirements. We investigate the unique optical constraints of transmitters in our proposed C-VLC system, and further propose a flexible hybrid underlay/overlay resource allocation approach to maximize the sum rate of SUs for the multi-cell C-VLC system, which is very different from radio frequency communication systems. Numerical results show that the proposed C-VLC system with hybrid overlay/underlay resource allocation achieves sum rate improvements of up to 29.2%, 20.6%, and 9%, compared with the conventional non-cognitive VLC system, the C-VLC system with only the underlay mode and the C-VLC system with only the overlay mode, respectively.